Analisis Kandungan Zat Gizi Lemak dan Natrium Klorida (NaCl) pada Jajanan Pentol di Sekolah Dasar Kelurahan Tondo Kota Palu - Hikmatullah Hikmatullah; Adillah Imansari; Masfufah Masfufah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Background: Pentol is a round-shaped snack that is popular with elemtary school children with a savory taste, affordable price, and easy to find in the school environment. However, uncontrolled consumption of pentol raises concerns about fat and sodium chloride (NaCl) content. Objective: This study aims to determine the levels of fat and NaCl contained in pentol snacks sold at Tondo Urban Village Elementary School, PaluCity. Method: This study used a Complate Random Design (RAL) on five pentol samples in five elementary school in Tondo Village, with two repetitions. Fat content was analyzed by the Soxhlet method, While sodium chloride (NaCl) content was analyzed by Mohr titration. The data were analyzed using the Kruskal-Wallis test. Findings: The fat content in five pentol sampels at Tondo Urban Village Elementary School ranged from 2,16-4,75% (maximum SNI limit of 10%), while sodium chloride content was 1,55-2,15% (maximum SNI limit of 2,5%). Statistical tests (p=0,4>0.05) showed no significant difference between samples. Although still below the SNI limit, the fat and sodium content is quite high for school children’s snacks. Conclusion: The fat and NaCl content of pentol sancks at Tondo Urban Village Elementary School, Palu City is still below the SNI limit, but the consumption of these snacks need to be limited. Implications: it is hoped that there will be further researchers who analyzed carbhohydrates, proteins and other additives such as preservatives in pentol snacks.